The Weibull Marshall–Olkin family: Regression model and application to censored data. Issue 16 (18th August 2019) - Korkmaz, Mustafa Ç.; Cordeiro, Gauss M.; Yousof, Haitham M.; Pescim, Rodrigo R.; Afify, Ahmed Z.; Nadarajah, Saralees
Abstract: We introduce a new class of distributions called the Weibull Marshall–Olkin-G family. We obtain some of its mathematical properties. The special models of this family provide bathtub-shaped, decreasing-increasing, increasing-decreasing-increasing, decreasing-increasing-decreasing, monotone, unimodal and bimodal hazard functions. The maximum likelihood method is adopted for estimating the model parameters. We assess the performance of the maximum likelihood estimators by means of two simulation studies. We also propose a new family of linear regression models for censored and uncensored data. The flexibility and importance of the proposed models are illustrated by means of three real data sets.